Death due to ricochet firearm injuries as a result of Soaring Gun Culture in India: A Hidden Evil in Indian Society and Its Implications: A Review with case report - Gupta, Aditi; Moondra, Ashok; Kumar Meena, Sachin (Journal of Forensic Medicine and Toxicology, 2025)
Gun Culture indicates that there is normalization of gun in society, but unaware of the consequences it holds for every one. It refers to exploitation of firearms due to easy availability and supply of illegal weapons from overseas at very low  cost. Different states like UP, Bihar, Punjab, J&K and Rajasthan had witnessed operation of unlicensed weapons. Due to  gun in many states India faces a serious issue. There are very strict laws for firearms in India, there are many loopholes  from where criminals and normal citizens acquire guns. There are so many reasons from portraying themselves as pow erful person or to threatening someone or to protecting and even killing someone. Few surveys shows that the numbers  of licensed firearms are very low as compared to unlicensed firearms. So many sever measures taken by government and  police to bring an end to the gun culture, but corruption and politics have given hope to the culprits. Thus, this mixed  article tries to bring out this situation, reasons and solutions for the prevailing evil form of gun culture in India with a  case report. In our case there was multiple open firing done with country made firearm at Jam-Packed place over a pity  argument between two local bhai/goons leading to death of one amongst them. After conducting a detailed postmor tem examination at our esteemed institute, it took a whole new different path in which Two Entry wounds & single Exit  wound is found with no evidence of any bullets, pellets or any other projectile object inside any body cavity. Internal  ricochet phenomenon was observed.
Keywords: Gun Culture; Firearm; Entry wound; Ricochet